PENGARUH KARAKTERISTIK KEWIRAUSAHAAN DAN INOVASI RASA TERHADAP KEBERHASILAN USAHA MIKRO PADA CV. STELLA CATERING MEDAN - Mohamad Reo Bangun; Dedi Iskandar Batubara (Universitas Islam Sumatera Utara, 2021)
This study aims to determine the effect of entrepreneurial characteristics and taste innovation on the success of micro-enterprises in CV. Stella Catering Medan. This study uses a quantitative descriptive method. the population is Consumer CV. Stella Catering from October 2020 to March 2021, as many as 55 people. The sampling technique of this study used a saturated sampling technique, so that the research sample was set as many as 55 people. As for the place of this research is CV. Stella Catering which is located on Jl. Stella I No.77, Kayu Raja, Kec. Medan Tuntungan, Medan City, North Sumatra, starting from January 2021 to July 2021. The results of this study indicate that entrepreneurial characteristics partially have a positive and significant effect on the success of micro-enterprises in CV. Stella Catering Medan. Taste innovation partially has a positive and significant effect on the success of micro-enterprises. At CV. Stella Catering Medan. The value of Fcount has a positive value of 53.421 Ftable = 2.78 and a significance of 0.000 0.05. This means that the characteristics of entrepreneurship and taste innovation simultaneously have a positive and significant effect on the success of micro-enterprises at CV. Stella Catering Medan. The value of Adjusted R Square (R2) is 0.660, indicating that the characteristics of entrepreneurship and taste innovation explain their effect on business success, which is 0.660 or 66%, while the remaining 34% is explained by other variables not examined in this study.